Vascular microRNA-204 is remotely governed by the microbiome and impairs endothelium-dependent vasorelaxation by downregulating Sirtuin1 - Ajit Vikram; Young-Rae Kim; Santosh Kumar; Qiuxia Li; Modar Kassan; Julia S. Jacobs; Kaikobad Irani (Nature Communications, 2016)
Commensal bacteria, the vast majority of which reside in the gut, are involved in development of many diseases, including atherosclerotic vascular disease. Here the authors show that these bacteria remotely increase expression of vascular microRNA-204, which targets Sirt1 in the endothelium to impair endothelial function.